2013
DOI: 10.1007/s10661-013-3168-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of seventeen endocrine disruptor compounds and their spatial and seasonal distribution in Ria Formosa Lagoon (Portugal)

Abstract: In spite of its outstanding ecological and touristic importance the Ria Formosa Lagoon shows signs of anthropogenic pollution. Nonetheless, until the present survey no studies had ever documented the measurement of natural and pharmaceutical estrogens (17β-estradiol, estrone, and 17α-ethynylestradiol), xenoestrogenic industrial pollutants (4-octylphenol, 4-nonylphenol, and their mono and diethoxylates and bisphenol A), phytoestrogens (formononetin, biochanin A, daidzein, genistein), and sitosterol in this area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
2
2
0
1
Order By: Relevance
“…Levels of salinity and pH were similar amongst sampling sites and identical to others measured in closely related aquatic systems Rocha et al 2013b;Rocha et al 2013c;Rocha et al 2013d). Concerning DO levels and with the exception of S 4 where these were extremely low, i.e.…”
Section: Physicochemical Datasupporting
confidence: 82%
See 2 more Smart Citations
“…Levels of salinity and pH were similar amongst sampling sites and identical to others measured in closely related aquatic systems Rocha et al 2013b;Rocha et al 2013c;Rocha et al 2013d). Concerning DO levels and with the exception of S 4 where these were extremely low, i.e.…”
Section: Physicochemical Datasupporting
confidence: 82%
“…SITO was identified in the past as an important component of seeds and vascular plants (Benassayag et al 2002). Comparing the levels of SITO measured in this study with those found in other Portuguese coastal waters, we concluded that its levels were similar or even slightly higher in Tagus estuary than in other aquatic coastal environments measured in other Portuguese coastal waters Rocha et al 2013b;Rocha et al 2013c;Rocha et al 2013d); however, further studies are needed to investigate the impact of the observed levels on Tagus estuary fauna.…”
Section: Industrial and Household Compoundssupporting
confidence: 63%
See 1 more Smart Citation
“…Bisphenol A (BPA) and 4-nonylphenol (NP) are also known EDCs ubiquitous in the aquatic environment [20]. The distribution of these EDCs has been found in coastal species as well as in the marine environment [21,22,23]. BPA is produced high volume from the manufactures used in a wide variety of consumer products [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Πιο συγκεκριμένα, κατά τη διάρκεια των θερινών μηνών παρατηρήθηκε αύξηση στις μετρούμενες συγκεντρώσεις των ουσιών λόγω της μείωσης των κατακρημνισμάτων αλλά και λόγω αύξησης της χρήσης και κατ' επέκταση της απόρριψής τους μέσω των ΕΕΛ π.χ. εξαιτίας πληθυσμιακών διακυμάνσεων λόγω τουρισμού (Rocha et al, 2013, Nam et al, 2014.…”
Section: Eννεϋλοφαινόληunclassified